The Effect of Competence, Integrity, Independence, Objectivity, on Audit Quality with the Moderating Variable of Risk-Based Auditing - Wati, Sinta; Puspitadewi, Andini; Dwiva, Sri Anna; Salta, Salta (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine and analyze the effect of competence, integrity, independence, objectivity, on audit quality with risk-based audit moderation variables at the Kuningan Regency Inspectorate. This research is quantitative research. The data used is primary data with a data collection method in the form of a questionnaire. The research data was processed using the IBM SPSS Statistics 26 program with a sample of 53 respondents. The results showed that auditor competence had no significant effect on audit quality. Meanwhile, auditor integrity, auditor independence and auditor objectivity have a significant effect on audit quality. Risk-based audit moderation variables are unable to moderate auditor competence, auditor integrity, auditor independence and auditor objectivity on audit quality.